Factors Affecting the HIV-Epidemic and its Differences in Sub-Saharan Africa – a Summary with Some Methodological Reflections (Nordic Journal of African Studies, 1996)
Factors Affecting the HIV-Epidemic and its Differences in Sub-Saharan Africa – a Summary with Some Methodological Reflections